2005
DOI: 10.1007/s00259-005-1917-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET in immunocompetent patients with primary central nervous system lymphoma: correlation with MRI and clinical follow-up

Abstract: PCNSLs demonstrate high FDG uptake and can be diagnosed by FDG-PET with high sensitivity. It seems that FDG-PET is suitable for early therapeutic monitoring after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 14 publications
4
69
2
3
Order By: Relevance
“…FDG-PET commonly identifies hypermetabolic lesions through increased uptake of FDG in PCNSL (2,3). Furthermore, FDG-PET was found to be suitable for evaluating therapeutic response (17). Our results suggested that FDG uptake was dependent upon GLUT3 rather than GLUT1 in PCNSL.…”
Section: Discussionmentioning
confidence: 73%
“…FDG-PET commonly identifies hypermetabolic lesions through increased uptake of FDG in PCNSL (2,3). Furthermore, FDG-PET was found to be suitable for evaluating therapeutic response (17). Our results suggested that FDG uptake was dependent upon GLUT3 rather than GLUT1 in PCNSL.…”
Section: Discussionmentioning
confidence: 73%
“…Karantanis et al reported that the mean T/N ratio was 2.45 in 13 PCNSLs at primary diagnosis [20]. Palmedo et al reported that the mean T/N ratio was 2.36 in 6 PCNSLs before initiation of chemotherapy [21]. Both reports did not mention steroid treatment; thus, there is a concern about the possible influence of corticosteroid application before the FDG PET study.…”
Section: Discussionmentioning
confidence: 93%
“…22 Distinguishing non-enhancing lymphomatous infiltration from vascular leukoencephalopathy and MTX-related leukoencephalopathy is challenging, particularly in elderly patients. In this setting, MRI spectroscopy 23 and PET scan 24 should be investigated as complementary tools.…”
Section: Discussionmentioning
confidence: 99%